A weight regain of 1.5 kg or more and lack of exercise are associated with nonalcoholic fatty liver disease recurrence in men - Naoko Nakanishi (Nature Portfolio, 2021)
Abstract The importance of maintaining the remission of nonalcoholic fatty liver disease (NAFLD) has been overlooked. Here we aimed to clarify factors causing NAFLD recurrence. In this retrospective cohort study over 10.8 ± 5.4 years, we investigated 1260 male health check-up participants diagnosed with NAFLD who achieved remission. The data were compared between the maintained remission and recurrence group. Among all participants, 618 (49.0%) showed NAFLD recurrence at the last visit. Participants in the maintained remission group continued to lose weight (72.7 ± 9.1, 68.7 ± 8.5 and 68.2 ± 8.9 kg), whereas those in the recurrence group lost and regained weight (72.9 ± 9.9, 69.7 ± 9.3 and 73.0 ± 10.4 kg). Receiver operating characteristic curve analysis showed a weight regain of + 1.5 kg as the cutoff value for recurrence. The proportion of regular exercisers at the last visit was 34.6% in the maintained remission group and 24.5% in the recurrence group (p < 0.0001). Multivariable analysis revealed the amount of weight regain (in 1 kg increments; adjusted odds ratio, 1.29; 95% confidence interval, 1.24–1.34) and regular exercise at the last visit (adjusted odds ratio, 0.67; 95% confidence interval, 0.55–0.89) were independently associated with recurrence. These findings demonstrate a weight regain of 1.5 kg or more and lack of exercise were associated with NAFLD recurrence.